The Practice of Multimodal Therapy : Systematic, Comprehensive, and Effective Psychotherapy - Lazarus, Arnold A. (Baltimore The Johns Hopkins University Press, 1993)
This book offers a practical, step-by-step guide to every phase of assessment and therapy, from the initial interview to follow-up treatments aimed at preventing relapse once formal treatment is over.
Include Index, Appendix and References
Keywords: Multimodal psychotherapy